Peran Motivasi Dan Lingkungan Keluarga Terhadap Minat Menjadi Akuntan - Aisyah, Nur; Windasari, Ihsanul (CV. ITTC INDONESIA, 2024)
This study aims to analyze the influence of motivation and family environment on the interest of Accounting students of Al-Qolam University in choosing a career as an accountant. In a dynamic working world, career choice is an important decision that is influenced by various factors, including individual intrinsic motivation and support from the family environment. This study uses a quantitative method by collecting data through a questionnaire to 15 Sharia Accounting students of Al-Qolam University. The data analysis technique used includes multiple linear regression tests to see the effect of the two independent variables (motivation and family environment) on the dependent variable (interest in becoming an accountant). The results of the study indicate that both motivation and family environment have a significant effect, both partially and simultaneously, on students' interest in becoming accountants. This finding has an important impact on the development of curriculum and educational strategies that can increase motivation and family support in supporting student careers in the field of sharia accounting.